Moving On? Memory and History in Griselda Gambaro's Recent Theater - Gail Bulman (Studies in 20th & 21st Century Literature, 2004)
For more than forty years, Argentine playwright Griselda Gambaro has dramatized the social and political climate of her homeland. This article examines three of her plays from the late eighties and early nineties, using both Freudian and performance theories, in order to show how these works document the range of emotions in post Dirty War Argentina and, at the same time, postulate ways of coping with the memories of those years. Beyond traditional memory-theater, these plays demonstrate the trauma of remembering by highlighting different phases in the memory process and by conceptualizing stages in the grief of a traumatized nation. In each play, Gambaro establishes a metaphor of thwarted or frustrated travel to question how much psychological progress Argentines and their nation have made since the Dirty War (1976-83).
Keywords: Argentine Literature; Griselda Gambaro; plays; Freudian theory; performance theory; Dirty War; memory; memory-theatre; grief; psychology